34‐1: Invited Paper: Can LCDs Outperform OLED Displays in Motion Picture Response Time?. Issue 1 (May 2017) - Peng, Fenglin; Chen, Haiwei; Wu, Shin-Tson
Abstract : A simple correlation between MPRT and LC response time, TFT frame rate, and duty ratio is established. At 120‐Hz frame rate, if the LC's response time is <2ms, then its MPRT would be comparable to OLED. To achieve CRT‐like MPRT, we could increase the frame rate or decrease the duty ratio.